2022
DOI: 10.3390/cells11233938
|View full text |Cite
|
Sign up to set email alerts
|

Mushroom Natural Products in Neurodegenerative Disease Drug Discovery

Abstract: The variety of drugs available to treat neurodegenerative diseases is limited. Most of these drug’s efficacy is restricted by individual genetics and disease stages and usually do not prevent neurodegeneration acting long after irreversible damage has already occurred. Thus, drugs targeting the molecular mechanisms underlying subsequent neurodegeneration have the potential to negate symptom manifestation and subsequent neurodegeneration. Neuroinflammation is a common feature of neurodegenerative diseases such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 145 publications
0
4
0
Order By: Relevance
“…Natural products for the management of PD have also been reported [108]. Additionally, several other natural products have been reported for the management of AD and other NDs [109,110]. The anti-cancer effects of GRk3 were also checked in Eca109 and KYSE150 cell lines (both esophageal squamous carcinoma cell lines), and it was observed that GRk3 suppressed proliferation and colony formation for both cell types.…”
Section: Ginsenoside Rk3 (Grk3)mentioning
confidence: 98%
“…Natural products for the management of PD have also been reported [108]. Additionally, several other natural products have been reported for the management of AD and other NDs [109,110]. The anti-cancer effects of GRk3 were also checked in Eca109 and KYSE150 cell lines (both esophageal squamous carcinoma cell lines), and it was observed that GRk3 suppressed proliferation and colony formation for both cell types.…”
Section: Ginsenoside Rk3 (Grk3)mentioning
confidence: 98%
“…[ 84 , 85 ]. The diverse metabolites of mushrooms also demonstrate potential neuroprotective properties [ 86 ]. In this section, we will briefly discuss recent investigations and the possible mechanisms of important mushroom bioactive constituents for the alleviation of the pathological manifestations of AD.…”
Section: Diversity Of Mushroom-derived Metabolites Beneficial To Ad A...mentioning
confidence: 99%
“…A sizable number of mushroom-isolated compounds display anti-inflammatory and antioxidant activity; therefore, most extracts and compounds described in the previous tables display such activities, thus enhancing the potential of mushroom-derived compounds as possible anti-AD treatment or adjuvants [ 115 ]. A recent review by Abitbol et al [ 37 ] efficiently covers the relationship between neuro-inflammation and the potential use of mushroom-derived compounds in AD, for this reason, the topic was not discussed in the present review.…”
Section: Mushrooms In Alzheimer’s Diseasementioning
confidence: 99%
“…The application of natural compounds is among the new features for therapies against AD, as described in recent reviews [ 25 , 35 , 36 ]. In this field, the potential role of mushrooms for AD treatment or prevention, has been highlighted [ 37 ]. Studies using mushroom extracts and compounds have demonstrated neuroprotective, neuromodulatory, and immunomodulatory activities, as well as an anti-inflammatory and antioxidant potential in neurodegenerative diseases [ 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation